Design, Preparation and Evaluation of Supramolecular Complexes with Curcumin for Enhanced Cytotoxicity in Breast Cancer Cell Lines - Hamdy Abdelkader; Adel Al Fatease; Zeinab Fathalla; Mai E. Shoman; Heba A. Abou-Taleb; Mohammed A. S. Abourehab (MDPI AG, 2022)
Curcumin is one of the most researched phytochemicals by pharmacologists and formulation scientists to unleash its potential therapeutic benefits and tackle inherent biopharmaceutic problems. In this study, the native β-cyclodextrin (CD) and three derivatives, namely, Captisol (sulfobutyl ether β-CD), hydroxypropyl β-cyclodextrin, and hydroxyethyl β-cyclodextrin were investigated for inclusion complexes with curcumin using two preparation methods (physical mixing and solvent evaporation). The prepared complexes were studied for docking, solubility, FTIR, DSC, XRD, and dissolution rates. The best-fitting curcumin: cyclodextrins (the latter of the two CDs) were evaluated for cytotoxicity using human breast cell lines (MCF-7). Dose-dependent cytotoxicity was recorded as IC50% for curcumin, curcumin: hydroxyethyl β-cyclodextrin, and curcumin: hydroxypropyl β-cyclodextrin were 7.33, 7.28, and 19.05 µg/mL, respectively. These research findings indicate a protective role for the curcumin: hydroxypropyl β-cyclodextrin complex on the direct cell lines of MCF-7.